2015
DOI: 10.1038/bonekey.2015.10
|View full text |Cite
|
Sign up to set email alerts
|

Molecular alterations that drive breast cancer metastasis to bone

Abstract: Epithelial cancers including breast and prostate commonly progress to form incurable bone metastases. For this to occur, cancer cells must adapt their phenotype and behaviour to enable detachment from the primary tumour, invasion into the vasculature, and homing to and subsequent colonisation of bone. It is widely accepted that the metastatic process is driven by the transformation of cancer cells from a sessile epithelial to a motile mesenchymal phenotype through epithelial-mesenchymal transition (EMT). Disse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 91 publications
2
24
0
Order By: Relevance
“…79,91,119 On a larger scale, physical features of the bone marrow microenvironment, including acidic pH, high extracellular calcium concentrations, and adjacent sinusoidal blood vessels, also enhance bone colonization by tumour cells (as they do for HSCs) and contribute to the vicious cycle, as described previously. 91,120 Hypoxia has been implicated both in the induction of tumour quiescence 74 and in egress of tumour cells from the marrow; 121 these effects, often driven by HIF signalling, are also seen in HSCs. 121123 As described above, hypoxia is a characteristic of the bone marrow, but whether the HSC niche (or tumour-homing niche) is always or necessarily hypoxic is still contentious, as HSCs and tumour cells are often found in close proximity to blood vessels.…”
Section: Haematopoietic Stem Cells and Tumour Cellsmentioning
confidence: 79%
See 2 more Smart Citations
“…79,91,119 On a larger scale, physical features of the bone marrow microenvironment, including acidic pH, high extracellular calcium concentrations, and adjacent sinusoidal blood vessels, also enhance bone colonization by tumour cells (as they do for HSCs) and contribute to the vicious cycle, as described previously. 91,120 Hypoxia has been implicated both in the induction of tumour quiescence 74 and in egress of tumour cells from the marrow; 121 these effects, often driven by HIF signalling, are also seen in HSCs. 121123 As described above, hypoxia is a characteristic of the bone marrow, but whether the HSC niche (or tumour-homing niche) is always or necessarily hypoxic is still contentious, as HSCs and tumour cells are often found in close proximity to blood vessels.…”
Section: Haematopoietic Stem Cells and Tumour Cellsmentioning
confidence: 79%
“…88,89 TGF-β (through Smad pathway signalling), hypoxia (through HIF-1α), and extracellular calcium (through Akt and MAPK pathways) alter gene expression within tumour cells in the bone microenvironment, enabling the survival and growth of these cells in the marrow cavity. 88,90,91 Many osteolytic tumour cells produce PTHrP, TGF-β, dickkopf-1, sclerostin, and RANKL; moreover, osteoblastic tumours often secrete bone morphogenic proteins and other growth factors (such as fibroblast growth factors and Wnt family members), but many of the mechanisms of osteoblastic lesion development remain undetermined. 92 Metabolic changes in tumour cells induced by their local microenvironment are also now recognized as important contributors to tumour growth and potential therapeutic targets.…”
Section: Cancer-related Disruption Of the Nichementioning
confidence: 99%
See 1 more Smart Citation
“…Bone generation and homeostasis are mainly operated by osteoclasts and osteoblasts (Bonnans, Chou, & Werb, ); RANKL expressed by cancer cells also promotes osteoclast differentiation and osteolytic bone metastasis in MDA‐MB‐231 metastasis models (Blake, Tometsko, Miller, Jones, & Dougall, ; Liu, Zhang, et al, ; Ottewell, O’Donnell, & Holen, ; Owen, Ye, Sanders, Mason, & Jiang, ). Our microarray analysis, however, showed that RANKL was not up‐regulated in MCF7‐BM cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression analysis showed increased RANKL and DKK-1 and decreased OPG; this was accompanied by increased MMP-9 and cathepsin K activity, suggesting increased bone resorption through elevated osteoclast activity [85]. This was proposed to be due to the stimulation of the mesenchymal stem cell niche and thereby promote DTC proliferation [86]. Similar to the breast cancer model, castration in mouse models of prostate cancer resulted in osteoclastic bone resorption, which increased bone metastasis [87].…”
Section: The Fate Of Dtcs In the Bone Marrowmentioning
confidence: 99%